Working for a Good Cause. (27th February 2014) - Dur, Robert; Zoutenbier, Robin
<x xml:space="preserve">Abstract</x> A rich literature in public administration has shown that public sector employees have stronger altruistic motivations than private sector employees. Recent economic theories stress the importance of mission preferences and predict that altruistic people sort into the public sector when they subscribe to its mission. This article uses data from a representative survey of more than 30, 000 employees from 50 countries to test this prediction. The authors find strong evidence of a mutually reinforcing role of altruism and mission alignment in sorting into the public sector, particularly among highly educated workers and among workers in less‐developed countries.